Hadith #28 - The Forty Hadith Qudsi - Jundub ibn Abdullah (The Forty Hadith Qudsi)
On the authority of Jundub ibn Abdullah (may Allah be pleased with him), who said that the Messenger of Allah (ﷺ) said: There was amongst those before you a man who had a wound. He was in [such] anguish that he took a knife and made with it a cut in his hand, and the blood did not cease to flow till he died. Allah the Almighty said: My servant has himself forestalled Me; I have forbidden him Paradise.
Grade: Sahih